1956
DOI: 10.1172/jci103386
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Aldosterone Secretion in Man: The Role of Fluid Volume 1

Abstract: Although aldosterone has recently been shown to play a part in the retention of sodium by edematous subjects (5), the factors governing its production have not been defined.It has been reported (6) that sodium restriction in normal subjects leads to increases in urinary aldosterone-like steroids, and that the quantities of such steroids are, other things being equal, inversely proportional to the amount of sodium excreted in the urine (5). In the studies reported here we have confirmed these reports in part, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
1

Year Published

1957
1957
1972
1972

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(50 citation statements)
references
References 15 publications
1
48
1
Order By: Relevance
“…However, water loading can lead to depressed proximal tubular reabsorption ofsodium, by intrarenal mechanisms (Martino & Earley, 1967). Furthermore, expansion of extracellular fluid and plasma volumes would cause reduced aldosterone production (Bartter, Liddle, Duncan, Barber & Delea, 1956) and, therefore, reduced tubular reabsorption of sodium.…”
Section: Discussionmentioning
confidence: 99%
“…However, water loading can lead to depressed proximal tubular reabsorption ofsodium, by intrarenal mechanisms (Martino & Earley, 1967). Furthermore, expansion of extracellular fluid and plasma volumes would cause reduced aldosterone production (Bartter, Liddle, Duncan, Barber & Delea, 1956) and, therefore, reduced tubular reabsorption of sodium.…”
Section: Discussionmentioning
confidence: 99%
“…2 It has previously been suggested that aldosterone secretion is regulated by some function of extracellular (8) Farrell (10) has suggested that aldosterone secretion is regulated principally by means of intracranial receptors, primarily measuring sodium concentration. Evidence from experiments in man, on the other hand, suggests that neither serum sodium concentration nor total body sodium can control aldosterone secretion, which can be made to vary independently of both (8). The (9).…”
Section: Discussionmentioning
confidence: 99%
“…It lhas been demonstrated that administration of sodium to normal individuals either by increasing dietary sodium intake or by giving an intravenous load of saline decreases aldosterone secretion or excretion (1)(2)(3)(4)(5)(6). The relationship between the response of the renin-angiotensin system and aldosterone to a sodium load has been less clearly defined.…”
Section: Introductionmentioning
confidence: 99%